Klasifikasi Ikan Cakalang dan Tongkol Menggunakan Convolutional Neural Network : Fish Classification of Skipjack and Mackerel Tuna Using Convolutional Neural Network - Wellifan Arrank Tonapa; Pinrolinvic D.K. Manembu; Feisy D. Kambey (Jurnal Teknik Informatika, 2024)
Abstract — Indonesia has a rich diversity of fish species, especially marine fish species. However, the abundance of fish species also poses challenges for the community in classifying each species. This challenge becomes even more significant when dealing with species that share similar physical characteristics, such as the pelagic fish group, which includes skipjack tuna (Katsuwonus pelamis) and mackerel tuna (Euthynnus affinis). Therefore, it is essential to have a profound understanding of fisheries science to accurately classify each fish species. With advancements in current technology, species classification can be automated using image-based classification methods. This research employs the Convolutional Neural Network (CNN) method to classify skipjack tuna and mackerel tuna species. The research results in a CNN classification model constructed using a transfer learning approach by leveraging the pre-trained ResNet50 model available in Keras Applications. The CNN Classification Model generated achieves a performance with a 95% accuracy rate, an average macro precision of 95%, an average macro recall of 95%, and an average macro F1 score of 95%. Key words— Classification; Convolutional Neural Network; fish species; Transfer Learning; Image. Abstrak — Indonesia memiliki banyak keanekaragaman spesies ikan, terutama spesies ikan laut. Namun, keberagaman spesies ikan yang banyak juga menimbulkan kesulitan bagi masyarakat dalam melakukan klasifikasi pada setiap spesies ikan yang ada. Apalagi, pada beberapa spesies ikan yang memiliki fisik yang hampir sama, seperti kelompok ikan pelagis, yaitu cakalang (Katsuwonus pelamis) dan tongkol (Euthynnus affinis). Oleh karena itu, penting untuk memiliki pemahaman mendalam tentang ilmu perikanan agar dapat melakukan klasifikasi yang benar terhadap setiap spesies ikan. Dengan kemajuan teknologi saat ini, pengklasifikasian spesies ikan dapat dilakukan secara otomatis menggunakan metode klasifikasi berdasarkan citra. Penelitian ini menggunakan metode Convolutional Neural Network (CNN) untuk mengklasifikasikan spesies ikan cakalang dan tongkol. Penelitian ini menghasilkan model klasifikasi CNN yang dibangun menggunakan pendekatan transfer learning dengan memanfaatkan model pre-trained ResNet50 yang tersedia di Keras Applications. Model Klasifikasi CNN yang dihasilkan mendapatkan nilai performa akurasi 95%, rata-rata makro precision 95%, rata-rata makro recall 95%, rata-rata makro f1 score 95%. Kata kunci — Citra; Convolutional Neural Network; Klasifikasi; Spesies Ikan; Transfer Learning.